Assessing different thiazolidine and thiazole based compounds as antileishmanial scaffolds - Schadich, Ermin; Kryshchyshyn-Dylevych, Anna; Holota, Serhiy; Polishchuk, Pavel; Džubak, Petr; Gurska, Sona; Hajduch, Marian; Lesyk, Roman (Bioorganic & medicinal chemistry letters, 2020)
The compounds from eight different thiazolidine and thiazole series were assessed as potential antileishmanial scaffolds. They were tested for antileishmanial activity against promastigotes of Leishmania major using in vitro primary screen and dose response assays. The compounds from six thiazolidine and thiazole series were identified as the hits with antileishmanial activity against L. major. However, the analyses of structure-activity relations (SARs) showed that the interpretable SARs were obtained only for phenyl-indole hybrids (compounds C1, C2, C3 and C5) as the most effective compounds against L. major promastigotes (IC50 < 10 µM) with low toxicity to human fibroblasts. For the scaffold of these compounds, the most significant SAR patterns were: free N3 position of thiazolidinone core, absence of big fragments at the C5 position of thiazolidinone core and presence of halogen atoms or nitro group in the phenyl ring of phenyl-indole fragment. As previous studies showed that these compounds also have activity against the two Trypanosoma species, Trypanosoma brucei and Trypanosoma gambiense, their scaffold could be associated with a broader antiparasitic activity.
Keywords: Parasitic Sensitivity Tests; Thiazolidines; Trypanosoma brucei gambiense; Humans; Indoles; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Leishmania major; lidé; Antileishmanial activity; Trypanosoma brucei brucei; molekulární struktura; Small Molecule Libraries; Molecular Structure; Trypanocidal Agents; trypanocidální látky; SAR; thiazolidiny; Thiazole core; knihovny malých molekul; fibroblasty; Thiazolidinone core; parazitické testy citlivosti; Fibroblasts